Urological adverse drug reactions of psychotropic medication in psychiatric inpatients – A drug surveillance report from German-speaking countries. (December 2021) - Winkler, Dietmar; Grohmann, Renate; Friedrich, Michaela-Elena; Toto, Sermin; Bleich, Stefan; Seifert, Johanna; Konstantinidis, Anastasios; Shariat, Shahrokh F.; Kasper, Siegfried; Pjrek, Edda
Abstract: Urological adverse drug reactions (UADR) are common during treatment with psychotropic medication. The aim of this study was to provide a systematic description of the differential profile of UADR of psychotropic drugs in a large naturalistic population. Data stems from psychiatric hospitals collected by AMSP (Arzneimittelsicherheit in der Psychiatrie), a continuous multi-center pharmacovigilance program in Austria, Germany, and Switzerland. 171 cases of severe UADR (0.037%) among a total population of 462 661 inpatients treated with psychotropic drugs in 99 psychiatric hospitals between 1993 and 2016 were examined. Urinary retention (129 cases, 0.028%) was the most common UADR followed by incontinence (23 cases, 0.005%) and nocturnal enuresis (16 cases, 0.003%). Risk of UADR was higher in patients with mania than in other diagnostic groups. Promethazine and haloperidol were the antipsychotics with the highest rate of UADR. Tricyclic antidepressants had a higher and selective serotonin reuptake inhibitors a lower risk for UADR than the respective other antidepressants. Amitriptyline and clomipramine were the most common causes of urinary retention and clozapine of urinary incontinence. This research improves our knowledge of the urological risk profiles of psychotropic drugs in inpatients and highlights compounds associated with higher or lower risk.